1993
DOI: 10.1021/jm00077a009
|View full text |Cite
|
Sign up to set email alerts
|

Novel antiasthmatic agents with dual activities of thromboxane A2 synthetase inhibition and bronchodilation. 2. 4-(3-Pyridyl)-1(2H)-phthalazinones

Abstract: A series of novel 4-(3-pyridyl)-1(2H)-phthalazinone derivatives which possess dual activities of thromboxane A2 (TXA2) synthetase inhibition and bronchodilation was synthesized, and their pharmacological activities were evaluated. While the length and the bulk of 2-alkyl substituents had no influence on either activity, the 2-substituents with polar groups reduced bronchodilatory activity. Furthermore, we introduced heteroaromatic nuclei into the 4-position of the phthalazinone and found that 1-imidazolyl (13a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…A modification of the technique of van Arman et al [8,9] was used. Guinea pigs of either sex (250−300 g) were fasted for 24 h. The test compound, was administered intraperitoneally at a dose of 10 mg/kg b.w.…”
Section: Protection Against Histamine-induced Bronchospasm On Consciomentioning
confidence: 99%
See 1 more Smart Citation
“…A modification of the technique of van Arman et al [8,9] was used. Guinea pigs of either sex (250−300 g) were fasted for 24 h. The test compound, was administered intraperitoneally at a dose of 10 mg/kg b.w.…”
Section: Protection Against Histamine-induced Bronchospasm On Consciomentioning
confidence: 99%
“…The bronchodilatory activity in vitro and in vivo was carried out for all the title compounds (Ia−p and IIa−l), using standard techniques. For in vitro activity, isolated guinea pig tracheal chain preparation was used following the method described by Castillo and deBeer [7] and for in vivo activity histamine chamber method [8,9] [10,11]. As shown in [1,2-c]quinazoline derivatives were prepared and characterized on the basis of their elemental analyses and spectral (IR, 1 H NMR and Mass) data.…”
mentioning
confidence: 99%
“…8,9 In finding new β-methoxyacrylate derivatives, we observed that, phthalazines attached to these pharmacophore were not studied. Phthalazin-1(2H)-one derivatives are of considerable interest due to their antidiabetic, 10 antiallergic, 11 vasorelaxant, 12 PDE4 inhibitor, 13 VEGF (vascular endothelial growth factor) receptor tyrosine kinase (for the treatment of cancer), 14 antiasthmatic, 15 and herbicidal 16 activities. A number of established drug molecules like Hydralazine, 17,18 Budralazine, 19,20 Azelastine, 21,22 Ponalrestat, 23 and Zopolrestat, 24 were prepared from the corresponding phthalazinones.…”
Section: Introductionmentioning
confidence: 99%
“…Phthalazin-1(2H)-ones are of considerable interest due to their antidiabetic [4], antiallergic [5], Vasorelaxant [6], PDE4 inhibitors [7], VEGF (vascular endothelial growth factor) receptor tyrosine kinases for the treatment of cancer [8,9], antiasthmatic agents with dual activities of thromboxane A2 (TXA2) synthetase inhibition and bronchodialation [10], herbicidal [11], like activities. A number of established drug molecules like Hydralazine [12,13], Budralazine [14,15], Azelastine [16,17], Ponalrestat [18] and Zopolrestat [19] are prepared from the corresponding phthalazinones.…”
Section: Introductionmentioning
confidence: 99%